The Growth of Red Meranti (Shorea leprosula Miq.) with Selective Cuttingand Line Planting in areas IUPHHK-HA PT. Sarpatim Central Kalimantan PERTUMBUHAN MERANTI MERAH (Shorea leprosula Miq) DALAM SISTEM TEBANG PILIH TANAM JALUR DI AREAL IUPHHK-HA ..... - Prijanto Pamoengkas; Rahmat Prasetia (Jurnal Silvikultur Tropika, 2014)
Shorea leprosula is a fast growing plant species in Borneo and has a tree structure that is straight and cylindrical, so this type are widely used in the production of plywood, furniture, and construction. Many of requests for production of red meranti (S. leprosula Miq) but the population continues to decline due to logging. Through the application of silvicultural techniques TPTJ with Intensive silvicultural in logged-over forest areas, the activities can be regarded as an effort to increase productivity and conservation. In an effort to realize the sustainability of the production function, then the success of the planting in the pathway is one important factor to be evaluated plant growth or productivity. In general, growth diameter plants of S. leprosula grown in line with TPTJ system in PT. SARPATIM plants 1 and 2 years of growth diameter distribution of age have not normal, while the old plants 3 and 4 years had a normal of distribution diameter growth here the number (frequency) of individuals (plants) found in many classes that represent the mean (average) of diameter stand, and diameter growth curvein the juvenile period.Growth of S. leprosula on track from age 1 to age 4 years to reach an average diameter increment (MAI) is the highest at the age of 1 year is equal to planting 1.54 cm/year and the lowest planted at the age of 3 years, which is 1 cm/year. Largest diameter found in the age of 4 years of planting 10.5 cm (mean 5.23 cm).Keyword : diameter, growth, production of natural forest, TPTJ silvicultural system, Shorea leprosula